Implementation of Work-Integrated Learning to Improve Vocational School Students' Work Readiness - Wahyuningsih, Rintatik; Noviani, Leny; Wardani, Dewi Kusuma; Sudarno, Sudarno; Siswanto, Romi (Mudir : Jurnal Manajemen Pendidikan, 2023)
Job readiness is a competency that must be possessed by Vocational High School (SMK) students. In order to create a qualified and work-ready workforce, Vocational High Schools equip their students with a set of work skills. However, the fact is that not all vocational students after graduation have sufficient skills to immediately enter the world of work, so they do not yet have the job readiness as expected from the business/industry world. This is because the learning and learning practices of SMK students are less relevant to the business/industry world and the utilization of Production Units in SMK is less optimized for learning practices. This study aims to: (1) determine the level of work readiness of SMK students; (2) identify teachers' efforts to improve student work readiness, and (3) determine the impact of the implementation of Work-Integrated Learning on increasing work readiness of SMK students. This research is a literature review based on descriptive qualitative methods. Based on the data from several journal articles analyzed, it can be concluded that the implementation of Work-Integrated Learning can improve the work readiness of SMK students.